Flucloxacillin in bone. Issue 8 (August 1978) - Unsworth, P F; Heatley, F W; Phillips, I
Abstract : Ten patients undergoing total hip replacement for osteoarthritis were each given intramuscular flucloxacillin about two hours preoperatively; bone and serum were sampled simultaneously at operation. Trabecular and compact bone were separated, partly dried, reduced to powders, and then extracted with buffer. The concentration of flucloxacillin in bone washings and serum was determined by well-diffusion assay. The mean concentration of flucloxacillin in serum was 8.9 mg/l, in trabecular bone washings, 1.3 mg/l, and in compact bone washings 0.9 mg/l. The amount of blood contaminating the bone washings was measured, and was calculated to account for at most 26% of the flucloxacillin present. The significance of these findings is discussed in relation to the prophylactic use of flucloxacillin in hip replacement surgery.